2003
DOI: 10.1007/s11746-003-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Two‐stage solvent extraction of seeds of Hibiscus abelmoschus linn: Lipid and FA compositions

Abstract: The lipid and FA compositions of TAG seed oil of ambrette (Hibiscus abelmoschus), contrary to earlier reports, were found to contain only a small amount of epoxy FA. Higher HBr absorption values were shown to be due to the presence of fragrance components of the seed coat in the oil derived from intact whole seeds. Cyclopropene/cyclopropane acids in the FAME were determined to be about 1.5% by GLC, while epoxy acids were less than 1% by two different methods. Based on the physicochemical characteristics and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Therefore, soxhlet method of extraction was considered as the complete extraction of neutral lipids and the process was carried out for 10 h. The higher yield of lipids may be due to the extraction of neutral lipids along with few percentages of polar lipids. It was reported that in the process of oil extraction generally hexane extract contain a few percentage of glycol lipids and phospholipids in comparison to the mechanical expression (Sahoo et al, 2003). The hexane extracted oil has higher acid value (1.1) and peroxide value (3.6) in comparison to screw press and supercritical CO 2 extract oil, therefore the hexane extracted oil is inferior in quality.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, soxhlet method of extraction was considered as the complete extraction of neutral lipids and the process was carried out for 10 h. The higher yield of lipids may be due to the extraction of neutral lipids along with few percentages of polar lipids. It was reported that in the process of oil extraction generally hexane extract contain a few percentage of glycol lipids and phospholipids in comparison to the mechanical expression (Sahoo et al, 2003). The hexane extracted oil has higher acid value (1.1) and peroxide value (3.6) in comparison to screw press and supercritical CO 2 extract oil, therefore the hexane extracted oil is inferior in quality.…”
Section: Resultsmentioning
confidence: 99%
“…Section 2 deals with the papers by Sahoo et al [13] where, in the seeds of Hibiscus abelmoschus, NL, GL, and PhL contained PA at the level of 22, 26, and 39% upon the extraction with methanol and 21, 37, and 41% in case of hexane extraction. Kundu et al [14] showed that, in the seeds of legumes, the content of PA in NL, GL, and PhL in pea was 13, 16, and 19% and that in bean was 11, 15, and 17%, respectively.…”
Section: Palmitic Acid In Neutral Glyco and Phospholipidsmentioning
confidence: 99%
“…Nechaev and Sandler [5] gave the content of total SFA (not PA) in the groups of lipids listed above (free, bound, and tightly bound) in the seeds of wheat (16,22, and 28%), rye (13,18, and 25%), maize (14, 33, and 36%) and buckwheat (20, 30, and 41%). They also cited the content of PA in free and bound lipids of maize embryos (14 and 20%, respectively) and cake (15 and 22%, respectively).…”
Section: Palmitic Acid In Neutral Glyco and Phospholipidsmentioning
confidence: 99%
“…The oils were converted to corresponding fatty acid methyl ester (FAME) as per our previous reported procedure (Sahoo et al 2003;Rout et al 2014).…”
Section: Gc-fid and Gc/ms Analysis Of Fatty Acid Methyl Esters And Unmentioning
confidence: 99%